PROTOTYPE PENGENALAN CANDI DI YOGYAKARTA BERBASIS AUGMENTED REALITY - Fatsyahrina Fitriastuti; Ryan Ari Setyawan; Helio Rofino Correia (Informasi Interaktif, 2022)
This study aims to introduce temple tourism objects in Yogyakarta in the form of three-dimensional objects, descriptions and maps using augmented reality technology with the markerless method and can be displayed on Android mobile devices. Augmented Reality is a technology that combines the real world with the virtual world. The markerless method was chosen because it makes it easier for users to track objects that exist in the real world without having to require objects on paper or brochures. The research method used is the Waterfall method which is a software development model that is carried out sequentially (the next stage will be run after the previous stage has been completed). With this application, it is hoped that it can become a medium of information for the public to obtain information about temple attractions in Yogyakarta. This application prototype was designed using Unity 3D, Blender, Vuforia SDK and Balsamiq Mockups 3. This application has been tested using the black box method with nine scenarios and all of them have worked as expected. Keywords: augmented reality, markerless, temple